HUBUNGAN ANTARA MANAJEMEN LAYANAN BIMBINGAN DAN KONSELING (BK) DENGAN KARAKTER MANDIRI SISWA DI MTS BANYUAYU KADUR PAMEKASAN - Ahmad Syarif Hidayat; Buna'i (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2021)
The problems that are the main study in this research, namely: first, is there a relationship between the management of guidance and counseling services with the independent character of students: second, how big is the relationship between the management of guidance and counseling services and the independent character of students. This study uses a quantitative approach with a descriptive type. Sources of data were obtained through questionnaires, interviews, observation, and documentation. The results of this study indicate that: 1. The relationship between the management of guidance and counseling services and the independent character of students at MTS Miftahul Ulum Banyuayu Kadur Pamekasan. 2. The purpose of guidance and counseling services. 2. Values ​​that can build students' independent character. 4. Development program for independent character-based guidance and counseling services. 5. Independent character education in the management of guidance and counseling services. Fostering good relations between teachers and students, between teachers and guardians of students, between teachers and the community or the surrounding environment.